Monetary policy implementation with ample reserves - Gara Afonso; Kyungmin Kim; Antoine Martin; Ed Nosal; Simon M. Potter; Sam Schulhofer-Wohl (Federal Reserve Bank of Atlanta, 2023)
We offer a parsimonious model of the reserve demand to study the tradeoffs associated with various monetary policy implementation frameworks. Prior to the 2007-09 financial crisis, many central banks supplied scarce reserves to execute their interest-rate policies. In response to the crisis, central banks undertook quantitative-easing policies that greatly expanded their balance sheets and, by extension, the amount of reserves they supplied. When the crisis and its aftereffects passed, central banks were in a position to choose a framework that has reserves that are (1) abundant-by keeping their balance sheets and reserves at the expanded level; (2) scarce-by vastly decreasing their balance sheets and reserves; or (3) somewhere in between abundant and scarce-by moderately decreasing their balance sheets and reserves. We find that the best policy implementation outcomes are realized when reserves are somewhere between scarce and abundant. This outcome is consistent with the Federal Open Market Committee's 2019 announcement to implement monetary policy in a regime with an ample supply of reserves.
Keywords: E42; E58; 330; federal funds market; monetary policy implementation; ample reserves